Utilization Potential of 30Year-old Oil Palm Trunks Laminated Veneer Lumbers for Non-structural Purposes - Wahab, Razak; Wan Samsi, Hashim; Mohamed, Azmy (2008)
Oil palm trunks found in abundant and considered as an agriculture waste were investigated as a possible alternative to future wood in utilization for non-structural purposes. The trunks are of no economic important in their natural form. However, once converted into the form of laminated veneer lumber (LVL) their properties improved tremendously. This paper highlighted properties of the LVL made from oil palm trunks at four (4) different positions comprising two (2) portions height and two (2) cross-sectional zones. These LVL have shown to behave differently when tested for their physical, mechanical and glue delaminating properties. Testing on all the LVL specimens were done in accordance with the Japanese Agricultural Standard, JAS No. 237: 2003.